A Panoramic View on Neurodegeneration, Its Connection with Microbiota and Its Therapeutics - Tejas Ganatra,; Pravin Tirgar, (International Journal of Scientific Research in Science and Technology, 2026)
Neurodegenerative diseases are becoming one of the leading causes of death globally and silently affecting the society. The major cause of neurodegeneration is accumulation of free radicals and reactive oxygen species that can induces cellular events of mitochondrial damage, activation of other necrotic cascades that results into neuronal death. One of the underlying causes of this accumulation is aging and reduced antioxidants in the body as well as the novel finding suggests that imbalance in Gut Brain Axis (GBA) is the major cause. Microbial gut flora plays an important role in balancing these free radicals as well as neural homeostasis. Due to aging and other causes this axis is damaged resulting into failure in repair mechanism against the neuronal death. Current therapy for neurodegeneration fails to treat the condition and only managing the symptoms because the therapy is intended for symptomatic cure only. Recent advances in therapy of neurodegeneration involves the repairing of system from root cause, by the means of gene therapy, immunomodulation, anti-oxidants therapy, balancing gut microbiota which can balance the Gut Brain Axis and thus can helpful to control several conditions, use of novel drug delivery system to improve the effectiveness of available treatments like nano-gel, nano-suspension, hydrogels, etc.
Keywords: Neurodegeneration; Parkinsonism; Alzheimer's disease; Gut brain axis; antioxidants